Marcas sonoras, voz, a lei da EIRELI e interpretação jurídica - Bezerra, Maurício José dos Santos (2015)
The registrability of sound marks and therefore the voice, very controversial Institute on Law Brazilian trademark,, post to find record of resistance by the regulatory agency, the federal agency INPI - National Institute of Industrial Property - the regrar the right to record sound marks from the use of the literal interpretation of Article 122 of Law 12,979 / 96, which, in its final part, provides that "visually perceptive distinctive sign". However, this institute has some inserts in Brazilian law, to speak of the Civil Code and the Federal Constitution, even if such provisions have direct application, at least until the issue of the law EIRELI (Law No. 12,441 / 2011). In this vein, the doctrine and jurisprudence have made use of hermeneutics and interpretative processes to develop legal thinking about the right of sound marks and voice, as the foreign trademark legislation, whether European, American and even countries Latin America, already willing to regulate the matter. Thus, this paper will address content on registrability of sound marks and the voice of law in Brazilian law, taking into account the rules of hermeneutics and comparative law.